2021
DOI: 10.1055/a-1467-2993
|View full text |Cite
|
Sign up to set email alerts
|

Improving Stroke Risk Prediction in the General Population: A Comparative Assessment of Common Clinical Rules, a New Multimorbid Index, and Machine-Learning-Based Algorithms

Abstract: We investigated stroke risks in a very large prospective cohort of patients with multimorbidity, using two common clinical rules, a clinical multimorbid index and a machine-learning (ML) approach accounting for the complex relationships among variables, including the dynamic nature of changing risk factors. Methods We studied a prospective US cohort of 3435224 patients from medical databases in a 2-year investigation. Stroke outcomes were examined in relationship to diverse multi-morbid conditions, demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 16 publications
3
57
0
Order By: Relevance
“…In this issue of Thrombosis and Haemostasis, Lip et al report on stroke risk prediction, using two common clinical rules (CHADS 2 , CHA 2 DS 2 -VASc scores), a clinical multimorbid index and a ML approach accounting for the complex relationships among variables, using a prospective U.S. cohort of 3,435,224 patients from medical databases. 27 This is a first large-scale investigation, with respect to the progressive risk factors for stroke, the difference between traditional statistical methods and ML-based algorithms in predicting stroke risk, together with the comparison of different AI ML approaches. The authors found that a clinical multimorbid index had higher discriminant validity values than common clinical rules, perhaps unsurprisingly given that more clinical variables were used.…”
mentioning
confidence: 99%
“…In this issue of Thrombosis and Haemostasis, Lip et al report on stroke risk prediction, using two common clinical rules (CHADS 2 , CHA 2 DS 2 -VASc scores), a clinical multimorbid index and a ML approach accounting for the complex relationships among variables, using a prospective U.S. cohort of 3,435,224 patients from medical databases. 27 This is a first large-scale investigation, with respect to the progressive risk factors for stroke, the difference between traditional statistical methods and ML-based algorithms in predicting stroke risk, together with the comparison of different AI ML approaches. The authors found that a clinical multimorbid index had higher discriminant validity values than common clinical rules, perhaps unsurprisingly given that more clinical variables were used.…”
mentioning
confidence: 99%
“…Integrating the ever-expanding information available, sifting through the risk categories and defining the risk trajectory for AFACS is becoming more of a challenge for a single individual and more appropriate for a clinical decision support system based on machine learning, especially given new advances in the latter for the prediction of AF and stroke. 28 Conflict of Interest None declared.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…54 Machine-learning approaches which account for risk factors' dynamic nature and multimorbidity may improve clinical stroke risk assessment over clinical scores, as demonstrated by a comparative study based on a large real-world data set. 55 Jones et al investigated the economic aspects of service interventions and put into light the cost-effectiveness of anticoagulation clinics, in particular targeting patients at high-risk and/or with suboptimal treatment, 56 a subject less often studied but nonetheless crucial in improving management praxis. While we require to acknowledge the dynamics of stroke risks and implement management flexibility accordingly, identifying specific groups of patients whose risks and benefits need to be weighted, also determines the success of anticoagulation strategies.…”
Section: Refining Anticoagulation Managementmentioning
confidence: 99%